Antiurolitihatic potency of Ketimun juice (Cucumis sativus L.) on white male rats using Kalkuli method - Sumi WIjaya; Farida L Darsono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
The aim of this research was to know the antiurolitihatic activities of Ketimun juice (Cucumis sativus L.) on white male rats which have been induced with hydroxyproline 30 % with a dose of 2,5 g/Kg BW. The 20% Ketimun juice (1.5 ml/100 g BW) and distilled water 1.5 ml/100 g BW were given the test animals orally. The parameter tests were characteristics of the kidney : the colour, shape, size and ratio of kidney weight /200 g BW and 24 hour urine on the first and the third days which included pH, 24 hour urine volumes and the calcium content in the urine. The data were analyzed using one sampel t-test. There were significant differences (p